(untitled) (diségno, 2024)
A comprehensive landscape architectural project In 1599, the Flemish painter Giusto Utens (?-1609) was commissioned by Duke Ferdinando I de’ Medici to create seventeen large-scale lunette paintings to decorate the banquet hall of the Villa di Artimino. These lunettes depicted the most representative villas constructed by the powerful Florentine family over a century and a half, forming one of the most distinctive landscape programs in history. The villas, with their houses, gardens, and landscapes, were located in various areas around Florence, symbolizing territorial occupation and the Medici family’s power, particularly during the eras of Cosimo the Elder, Lorenzo the Magnificent, and Cosimo I, Grand Duke of Tuscany. [read more]